1976
DOI: 10.1073/pnas.73.9.3107
|View full text |Cite
|
Sign up to set email alerts
|

Interferon, double-stranded RNA, and protein phosphorylation.

Abstract: We reported earlier that the addition of double-stranded RNA and ATP increases the endonuclease activity more in an extract of Ehrlich ascites tumor cells which have been treated with an interferon preparation than in a comparable extract from control cells. We repo here that the addition of double-stranded RNA to an extract from Ehrlich ascites tumor cells which have been treated with an interferon preparation [or with the interferon inducer poly(I).poly(C)J promotes the phosphorylation by Tris-CI at pH 7.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
99
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(102 citation statements)
references
References 25 publications
3
99
0
Order By: Relevance
“…The hemin-controlled inhibitor of protein synthesis has been studied in reticulocytes and is activated by various stimuli including hemin deprivation and heat treatment (6,19). The double-stranded RNA (dsRNA)-activated inhibitor (DAI) is induced by interferon, and its activity is dependent on dsRNA (12,18,20,31). Translational control mediated by DAI protein kinase has also been studied in adenovirusinfected cells, in which it has been found that two RNA polymerase III transcripts from the adenovirus genome are expressed at high levels and are required for efficient translation of adenovirus mRNAs late after infection (27).…”
mentioning
confidence: 99%
“…The hemin-controlled inhibitor of protein synthesis has been studied in reticulocytes and is activated by various stimuli including hemin deprivation and heat treatment (6,19). The double-stranded RNA (dsRNA)-activated inhibitor (DAI) is induced by interferon, and its activity is dependent on dsRNA (12,18,20,31). Translational control mediated by DAI protein kinase has also been studied in adenovirusinfected cells, in which it has been found that two RNA polymerase III transcripts from the adenovirus genome are expressed at high levels and are required for efficient translation of adenovirus mRNAs late after infection (27).…”
mentioning
confidence: 99%
“…A protein kinase(s), 2'-5'A synthetase [responsible for the formation of a series of 2'-5'-linked oligo(adenylic acid) triphosphate (2'-5'A) inhibitors of protein synthesis in which the trimer pppA2'p5'A2'p5'A is predominant], and a nuclease may all be involved in this inhibition (4)(5)(6)(7)(8)(9)(10)(11)(12). The kinase is thought to phosphorylate the smallest subunit of initiation factor eIF2, as appears to be the case in rabbit reticulocyte lysates, on inhibition of protein synthesis by a number of agents, including dsRNA (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…A characteristic example is human lymphoid cells which exhibit varied sensitivity to homologous interferon (Adams et al, 1975). Although there is general agreement that a number of enzymic activities are elevated in cells which have been treated with interferon (Marcus et al, 1975;Meldolesi et al, 1977;Lebleu et al, 1976;Roberts et al, 1976;Hovanessian et al, 1977;Kerr et al, 1977, Kerr & Brown, 1978De Ley et al, 1979;Schmidt et al, 1979) no one as yet has correlated any of these enzymes with the sensitivity of cells to interferon. Double-stranded RNA-dependent 2'-5' oligo(A) synthetase which converts ATP to oligonucleotides with 2'-5' phosphodiester bonds (Kerr & Brown, 1978) is one of these enzymes which occurs widely in cells and is generally induced with interferon, although certain cells carry this enzymic activity even if not treated with interferon (Stark et al, 1979;Werhaegen et al, 1980).…”
Section: Discussionmentioning
confidence: 99%